Sensor Fiber Optik Dari Bahan Fiber Optik Polimer Untuk Pengukuran Refractive Index Larutan Gula - Sari, Nila Wulan; Marzuki, Ahmad; R, Riyatun (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2012)
This paper presents an experimental result on developing an optical fiber sensor for measuring refractive index of sugar solution. Sensor was developed using polymer optical fiber with diameter of 3 mm. This sensor is working based on intensity modulation due to reflection. Light coming out from the transmitter optical fiber is reflected by a mirror to the receiver optical fiber. Due to the variation of sugar concentration in solution surrounding this sensor, the way of light entering the fiber receiver depends on the sugar concentration (numerical aperture). It is clear from the experiment that light intensity detected by photodetector (represented by electric voltage) is linearly dependent (R2 = 0.987) on the variation of sugar solution refractive index.